Chemical Tools and Biochemical Assays for SUMO Specific Proteases (SENPs) - Jia, Yuqing (ACS Chem Biol, 2019)
[Image: see text] SUMOylation is a reversible and highly dynamic post-translational modification of target proteins by small ubiquitin-like modifiers (SUMO). It is orchestrated by SUMO-activating, -conjugating, and -ligating enzymes in a sequential manner and is important in regulating a myriad of predominantly nuclear processes. DeSUMOylation is achieved by SUMO-specific proteases (SENPs). Deregulation of SUMOylation and deSUMOylation results in cellular dysfunction and is linked to various diseases, including cancer. In recent years, SENPs have emerged as potential therapeutic targets. In this review, we will describe the inhibitors and activity-based probes of SENPs. Furthermore, we will summarize the biochemical assays available for evaluating the activity of SENPs to identify inhibitors.